(2,4-Dimethoxy-benzyl-idene)-2-hydroxy-benzohydrazide ethanol solvate. - Yehye, W.A.; Ariffin, A.; Ng, Seik Weng (International Union of Crystallography, 2008)
In the planar title mol-ecule, C(16)H(16)N(2)O(4)·C(2)H(6)O, the planar Schiff base molecule is linked to the ethanol solvent mol-ecule by a hydr-oxy-amide hydrogen bond. The hydr-oxy group of the ethanol mol-ecule is a hydrogen-bond donor to the double-bonded N atom of an adjacent Sciff base, pairs of interactions taking place across a center of symmetry and giving rise to a hydrogen-bonded dimer.